A Pragmatic Strategy on Empowering Rural Women for Nutritional Security and Income Enhancement - Satyapriya, Premlata Singh, V. Sangeetha,V. Lenin, Sudipta Paul, Sukanya Barua, Sitaram Bishnoi, Ravi Shankar, Himanshi Rathore & Satyaprakash (Indian Journal of Extension Education, 2023)
India is the largest producer of milk, wheat and fruits, and the second largest producer of rice, pulses and vegetables in the world. On the other hand it has 194 million undernourished people and tops the ‘world hunger list’ as well. Undernutrition has been a persistent challenge and affects the quality of human capital and workforce in India directly besides pushing the vulnerable and poor in a vicious cycle of poverty and low productivity. Women farmers play an active and important role in agriculture. In developing countries like India, women are the building blocks managing the food security of their family, unfortunately, they are also suffering from malnutrition as they always tend to neglect their own health. There is a need to shift from the policies of food security to nutritional security which pays concurrent attention to undernutrition (not eating calories), protein hunger and hidden hunger. In lieu with this, Division of Agricultural Extension, ICAR-IARI has initiated steps ahead by leading a project funded by UNDP towards enhancing nutritional security and empowering farm women’s of India. The current study is based on the results and outcomes of the above stated project, in which we surveyed and trained the total of 1500 women’s. The study was conducted in the selected villages of districts Mewat, Jhajjar and Sonipat of Haryana state. Results revealed that there was about 51.07 percent increment in the level of knowledge of the women in terms of nutrition, value addition and post-harvest management of the nutri products such as Bajra ladoos, Bajra pops, Soy tofu, Soy milk etc. Additionally, based on the pre and post-tests, women’s were found to have increased level of entrepreneurial motivation (25.65%) to start their own ventures for their improved nutritional as well as socio-economic development. This model can be replicated in other locations which will yield positive impact in terms of economic empowerment and nutritional security.